(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the article analyzes the legal relations related to the franchise contract in Uzbekistan based on national legislation and the opinions of scientists who have researched this contract, and shows modern trends in this regard. The role of the franchising contract in the development of the market economy is highlighted, and based on these analyses, the views on the complex business license (franchising) are stated. Based on the analysis of the complex business license (franchising) issues in Uzbekistan, conclusions and recommendations were put forward.